math105samplefinalsolution

# math105samplefinalsolution - The University of British...

This preview shows pages 1–3. Sign up to view the full content.

This preview has intentionally blurred sections. Sign up to view the full version.

View Full Document
This is the end of the preview. Sign up to access the rest of the document.

Unformatted text preview: The University of British Columbia Sample Final Examination - 2009 Solutions Mathematics 105 1 . Short-Answer Questions . (a) The level curve is given by x 2 + y 2 = c for some constant c . Since 1 2 +2 2 = c , we get x 2 + y 2 = 5. Thus, the radius is √ 5. (b) ∂f ∂y =- sin x y- x y 2 = x y 2 sin x y . Hence, we get ∂f ∂y ( π, 2) = π 2 2 sin π 2 = π 4 . (c) Solving the system ∂z ∂x = 2 x- 2 y + 12 = 0 ∂z ∂y =- 2 x- 2 y = 0 , we get x =- 3 and y = 3. Hence, the point is (- 3 , 3). (d) lim h → f ( x + h,y )- f ( x,y ) h = ∂f ∂x = 2 2 x- 3 y . (e) C ( x ) = Z (0 . 3 x 2 + 2 x ) dx = 0 . 3 x 3 3 + x 2 + c . Since 2000 = C (0) = c , we have C ( x ) = . 1 x 3 + x 2 + 2000. It follows that C (20) = 0 . 1(20 3 ) + 20 2 + 2000 = 3200. (f) Let u = ln5 x . Then du = 5 5 x dx = dx x and Z ln(5 x ) x dx = Z udu = u 2 2 + c = (ln5 x ) 2 2 + c . (g) Let u = sin- 1 x and dv = dx . Then du = 1 √ 1- x 2 dx and v = x . Therefore, Z sin- 1 xdx = x sin- 1 x- Z x √ 1- x 2 dx . Let w = √ 1- x 2 . We have dw =- x √ 1- x 2 dx . Thus, Z sin- 1 xdx = x sin- 1 x- Z- dw = x sin- 1 x + w + c = x sin- 1 x + p 1- x 2 + c . (h) Z 1 πe- 2 x dx =- π 2 e- 2 x 1 = π 2 1- 1 e 2 . (i) Average price = 1 30- 10 Z 30 10 50 e- . 05 x dx = 5 2 Z 30 10 e- . 05 x dx = 5 2 e- . 05 x- . 05 30 10 = 50( e- . 5- e- 1 . 5 ). (j) 5 = √ 2 Z 6 3 p f ( x ) dx . Hence, Z 6 3 p f ( t ) dt = 5 √ 2 . 1 (k) A ( t ) = Z t 1 2 dt = 2 3 t 3 2 . The integrating factor is e 2 3 t 3 2 . (l) 1 = Z ∞ cxe- 2 x dx = c Z ∞ xe- 2 x dx = c 1 4 . Hence, c = 4. (m) The area is Z π/ 2 (sin x- sin 3 x ) dx = Z π/ 2 sin x (1- sin 2 x ) dx = = Z π/ 2 sin x cos 2 xdx = Z 1- u 2 du =- u 3 3 1 = 1 3 . ↑ u = cos x du =- sin xdx (n) 0 . 5 = Z b 2 1 4 e- t/ 4 dt = 1 4 (- 4) e- t/ 4 b 2 =- e- b/ 4 + e- 1 / 2 . Hence, e- b/ 4 = e- 1 / 2- . 5,- b 4 = ln e- 1 / 2- . 5 or b =- 4 ln e- 1 / 2- . 5 ....
View Full Document

{[ snackBarMessage ]}

### Page1 / 6

math105samplefinalsolution - The University of British...

This preview shows document pages 1 - 3. Sign up to view the full document.

View Full Document
Ask a homework question - tutors are online